2014
DOI: 10.1038/srep06434
|View full text |Cite
|
Sign up to set email alerts
|

Di-(2-ethylhexyl) phthalate inhibits DNA replication leading to hyperPARylation, SIRT1 attenuation and mitochondrial dysfunction in the testis

Abstract: Di-(2-ethylhexyl)-phthalate (DEHP) is a ubiquitously used endocrine disruptor.There is widespread exposure to DEHP in the general population which has raised substantial public concern due to its potential detrimental health effects. It is particularly pertinent to investigate the molecular mechanisms of its testicular toxicity which are largely unknown. By feeding male rats DEHP for 2 weeks, rat spermatogenesis became disrupted, resulting in a decreased number of spermatocytes and spermatids. Since rapidly di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 44 publications
(57 reference statements)
3
36
0
2
Order By: Relevance
“…[37][38][39] Phthalates cause mitochondrial dysfunction in mouse Leydig cells, and in the testis. 40,41 A recent meta-analysis found that the prevalence of mitochondrial disease in children with autism spectrum disorder was 5%. 42 Clinical evaluation and laboratory analyses (blood lactate, pyruvate, alanine, total carnitine, creatine kinase, ammonia, aspartate aminotransferase, and alanine aminotransferase) did not indicate mitochondrial disease in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] Phthalates cause mitochondrial dysfunction in mouse Leydig cells, and in the testis. 40,41 A recent meta-analysis found that the prevalence of mitochondrial disease in children with autism spectrum disorder was 5%. 42 Clinical evaluation and laboratory analyses (blood lactate, pyruvate, alanine, total carnitine, creatine kinase, ammonia, aspartate aminotransferase, and alanine aminotransferase) did not indicate mitochondrial disease in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of DNA damage leads to SIRT1 (regulator of mitochondrial function) attenuation and thereby suppresses testicular ATP levels. The DEHP-induced attenuation of ATP levels may be a crucial problem to male fertility since the motility of spermatozoa depends on sperm ATP [ 37 ].…”
Section: Dehp and Testicular Toxicitymentioning
confidence: 99%
“…Kasahara et al [96] indicate associations between DEHP administration and increased production of ROS and selectively decreased GSH and ascorbic acid in the testis with a consequent induction of rat sperm cell apoptosis leading to testicular atrophy after in vivo DEHP exposition. More specifically, the results provided by Li et al [108] when male rats were fed DEHP for 2 weeks. The result was that the spermatogenesis became disrupted with decreased spermatocytes and spermatids counts and in addition, DEHP (20, 100, 500, to 1000 mg/kg) appeared to inhibit DNA replication.…”
Section: Monoethylhexyl Phthalate (Mehp)mentioning
confidence: 99%